Epistemology of Reconstruction of Prophetic Thinking Methodology In The View of Musa Asy'arie - Zaprulkhan, Zaprulkhan (KALAM, 2019)
Prophet Muhammad besides being a leader and statesman, he was also a great thinker. Aside from being a master educator, he was also a rational-transcendental thinker. But not many of us are able to see the Prophet Muhammad in the aspect of his thinking. In the perspective of Musa Asy’arie, the most important aspect for us to emulate in the Prophet Muhammad is his aspect of thought. When we are able to emulate the dimensions of the Prophet's thinking, we will be able to apply the method of prophetic thinking. This paper raises several epistemological questions: What is the meaning of prophetic thinking? How is the epistemology of reconstruction prophetic thinking in the perspective of Musa Asy’arie? This study uses philosophical and historical approach. It is found that in the view of Musa Asy’arie prophetic thinking is transcendental rational thinking by uniting between aspect rational and spiritual aspects. While the epistemology of prophetic thinking is a systemic integrative thinking process between transcendental awareness and scientific methodological and technological thinking in order to find God's laws that can produce knowledge, science and technology. This paper will elaborate epistemology of reconstruction of prophetic thinking metodology in the view of Musa Asy’arie.